EVALUASI UPAYA PENGOBATAN SENDIRI (SWAMEDIKASI) MENGGUNAKAN OBAT ANALGETIKA-ANTIPIRETIKA PADA MASYARAKAT DESA JERUJU BESAR KALIMANTAN BARAT - Yulia Wardati (Jurnal Sabdariffarma, 2022)
Self-medication requires a good knowledge in order to run well. This study was conducted to determine the relationship and strength of the relationship in the selection of antipyretic analgesic drugs associated with age, education and occupation by the people of Jeruju Besar Village. This type of research is non-experimental with a questionnaire tool. Sampling using purposive sampling method. Respondents in this study were 378 respondents. The results showed that the people of Jeruju Besar Village were right in choosing the medicine for fever, headache and pain. Respondents received information on drug selection through health workers by 58.7% and the reasons for self-medication to recover quickly were 74%. The majority of respondents aged 40 years 52.6%, while the level of education is moderate - high 52.4%. Based on the Multiple Correlation test the strength of the relationship was obtained Perfect Correlation or perfect knowledge (0.981) and education (0.872), Strong Correlation occupation (0.698) and age (0.633). The conclusion of this study is that there is a relationship between the level of education, knowledge, on the use of antipyretic analgesic drugs.